International Legal Scholarship and the Quest for Integrating Democratic and Participatory Principles in the Definition of Global Public Goods - Eva Kassoti (UCL Journal of Law and Jurisprudence, 2018)
This contribution purports to critically examine the ways in which modern international legal scholarship has come to grips with the question of bridging the ‘democratic participation gap’ in the context of defining and prioritising global public goods. It begins by asserting that core tenets of legal positivism, such as State sovereignty and consent, are deeply undemocratic, or that, at a minimum, they are capable of operating in a deeply undemocratic way, thereby casting doubt on whether classic international law can be seen as the solution to the problem of democratic participation. Against this background, the article continues by exploring two alternative theoretical frameworks for bridging the ‘participation gap’. The global administrative law project is examined and rejected as its main focus on accountability, rather than democracy, implies that it lacks ambition when it comes to the question of broadening decision-making processes. The focus turns next to global constitutionalism. It is argued that, in reality, this version of constitutionalism does not really offer any new analytical and normative insights; traditional legal thinking is anything but unfamiliar with the conceptual distinction between direct and indirect participation. The article concludes by canvassing some remarks on a common mindset of the discipline: the discipline’s knee-jerk response to the challenge of defining global public goods illustrates the unease felt by international lawyers to deal with questions of global governance without transferring them into the realm of law. For full text, please click here
Keywords: legal theory; global public goods; international law